Nongonococcal Septic Arthritis in the Adult - Moleiro, Filipa; Monteiro, Nadine; Lérias, Graça; Mello e Silva, Alberto (Portuguese Journal Internal Medicine, 2015)
Septic arthritis (SA) is a rare rheumatological emergency associated with high mobidity and mortality rates. Functional outcome of the involved joint and patient survival depend mainly on early recognition and timely onset of the appropriate therapy. Despite the development and availability of laboratory and image tests, clinical suspicion remains the most important factor for a prompt diagnosis. Empirical antibiotic therapy is based on the host risk factors and the result of synovial fluid gram stain. Definitive diagnosis is achieved after isolating the pathogenic agent in synovial fluid. Staphylococcus aureus is the most commonly isolated agent and, in recent years, have witnessed the increased importance of the methicillin resistant strain. Most published guidelines on diagnostic approach and treatment management are based on expert consensus. It is essential to strengthen the importance of prompt diagnosis in order to reduce SA morbidity and mortality rates. Therefore, authors consider relevant to review the clinical approach, additional diagnostic tests, treatment and management of complications. Only nongonococcal SA in the adult will be reviewed